METHOD OF DESIGNING ANTENNAS BY SYNTHESIS OF A BAND FILTER - MISHAN, Viktor; KARPOVA, Lesia; TSIMAR, Valerii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A novel antenna design technique is proposed, which offers bandwidth enhancement up to the limits defined by element radiation efficiency. The employed technique is referred as frequency pulling (FP) as it mimics the insertion loss design methodology of bandpass filters. This is essentially a wideband matching approach pushing the antenna efficiency to the limits set up by radiation efficiency. There are three options towards this trend: (1) first to enhance a single element bandwidth (compact element) exploiting its possibly multiple symmetrical feeding points as distinct resonator ports, (2) frequency pulled array as to design a small antenna array (less than about 10 elements) where eachelement acts as a resonator and (3) second order frequency-pulled array as to build a small array using compact elements of category (1). Similar to the band-pass filter design, all antennas or distinct-port circuits resonate at the same resonant frequency when isolated, cascading two or more of them; FP yields to multiple-overlapping successive resonances in their overall response. Although the proposed technique is general within this first effort, it is applied to simple patch antenna elements exhibiting multiple symmetrical feeding points, namely two-for rectangular, four-for square and five-for pentagonal. The third option is applied to an array of three compact 4-feeding point square elements offering triple bandwidth with respect to the already wideband single element. However, this is achieved at the expense of a significant beam squint. Thus, in general, these wideband compact elements should be used within a classical array design. Further bandwidth enhancement using FP to antenna elements with inherent multiple resonances as patches with slots or truncated edges constitutes our next task. Their inherent wider bandwidth in radiation efficiency is expected to allow multiply higher bandwidths when exploited with our FP technique.
Keywords: antenna arrays; antenna feeds; band-pass filters; broadband antennas; impedance matching